2022
DOI: 10.1016/j.mtbio.2022.100204
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamomum verum-derived bioactives-functionalized gold nanoparticles for prevention of obesity through gut microbiota reshaping

Abstract: Existing drugs have limited success in managing obesity in human due to their low efficacy and severe side-effects. Surface-modified gold nanoparticles have now received considerable attention of researchers for efficient biomedical applications owing to their superior uptake by cells, biocompatibility, hydrophilicity and non-immunogenicity. Here we prepared Cinnamomum verum derived bioactives-functionalized gold nanoparticles (Au@P-NPs) and assessed their impact on obesity and related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…65 Another study revealed that bioactive-functionalized AuNPs could alter systemic metabolites through gut microbiota for prevention of obesity. 66 These studies indicate that modifying the surface of AuNPs could be a strategy to eliminate potential negative effects. Significantly, the biological safety of biomaterials in vivo is always a crucial issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Another study revealed that bioactive-functionalized AuNPs could alter systemic metabolites through gut microbiota for prevention of obesity. 66 These studies indicate that modifying the surface of AuNPs could be a strategy to eliminate potential negative effects. Significantly, the biological safety of biomaterials in vivo is always a crucial issue.…”
Section: Discussionmentioning
confidence: 99%
“…coli in the gut more effectively than levofloxacin, without harming intestinal microflora . Another study revealed that bioactive-functionalized AuNPs could alter systemic metabolites through gut microbiota for prevention of obesity . These studies indicate that modifying the surface of AuNPs could be a strategy to eliminate potential negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 presents some recent advancements in detection and diagnosis for biosensing applications. 96–128 Sensors based on diverse functionalities and constituents, such as capacitive pressure sensing, healing wearable sensors, pressure, wireless, FRET-based genetically encoded sensors for silver ions, oxygen sensors on an optofluidic platform, location tracking, metamaterials based on soft tactile, electrospinning-based PVDF-TrFE nanofiber sensors, glycine–chitosan-based biodegradable piezoelectric sensors, and DNA-regulated CRISPR-Cas12a sensors, represent important advances in the biosensor field. 96–106 Detection is based on diverse approaches, including paper-based devices, 3D-printing electrochemical, MoS 2 quantum dots, 2D nanomaterial-enhanced plasmonic functionality, smartphone-integrated colorimetric, PVDF-TrFE nanofiber, electronic, machine learning, fluorescent DNA, non-enzymatic glucose, and silicon nanowire biosensing platforms for the (bio)detection of various analytes ranging from metal, pollutants, cells, genetic materials, and even post-translational modification.…”
Section: Recent Advancements In Sensor-based Detection and Diagnosismentioning
confidence: 99%
“…4 Moreover, the prospect of their further use is facing great challenges owing to their severe adverse effects, such as diarrhea, headache, fecal incontinence, and dyspepsia. 5 The gut microbiota, known as a "second genome", is crucial for disease prevention and enhances human health. 6 Obesity development has been acknowledged as a significant contributor to gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, the prospect of their further use is facing great challenges owing to their severe adverse effects, such as diarrhea, headache, fecal incontinence, and dyspepsia. 5…”
Section: Introductionmentioning
confidence: 99%